Logistics approach to the transportation of products from farms and agricultural enterprises - Abdullayev Rustam; Abduvakhitov Shakhboz (BIO Web of Conferences)
The foreign economic strategy of the activities of farms and rural enterprises, as well as other producers of agricultural products, is one of the main parts of the foreign economic policy of the Republic of Uzbekistan in the process of entering the world market. The article examines the logistics approach to transporting products from farms and agricultural enterprises focuses on the comprehensive organization and optimization of all stages of transportation from the point of production to the end consumer. This approach aims to ensure efficiency, minimize costs, and preserve product quality.